SERBIAN AGRO-INDUSTRY-POTENTIALS AND PERSPECTIVES - Savić, Ljubodrag; Bošković, Gorica; Mićić, Vladimir (Economics of Agriculture, 2016)
This paper analyses agriculture and the food industry as dominant sectors of the Serbian agro industrial complex. The goal of the research is to stress the signifcance of the agro industry for economic development and the directions of its future development, as well as the signifcance of the agricultural and industrial policy for its development. For the purpose of a hypothesis the testing indicators of development, structural changes and work productivity will be analyzed. A correlation analysis is used to determine the character of dependence and the impact of the agriculture and food industry on key indicators of economic growth. The comparative method is used for a comparative analysis of the structural changes of Serbian agriculture as well as for some of the new EU member states. Research results show that new EU member states adapt the structure of their agriculture more effciently to the new demands of development, resulting in the agro industry creating a greater added value which influences overall economic development. The great potential of the Serbian agro industrial complex could be a very good foundation for effcient agro industrial growth and an increase of competiveness on EU and Russia markets, as well as on numerous markets of other world countries, having in mind that overall demands for ecologically healthy food will grow rapidly in the following period.